2010
DOI: 10.1016/j.seizure.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and tolerability of the ketogenic diet in drug-resistant childhood epilepsy—The Austrian experience

Abstract: Despite the retrospective nature of the study and the inhomogeneous patient sample, we found good long-term effects of the KD on seizure frequency, EEG and neurological development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 41 publications
5
57
0
3
Order By: Relevance
“…These results are similar to those reported from other centers and similar to our experiences with the KD in other epilepsy syndromes (Dressler et al, 2010;Kossoff et al, 2010;Maydell et al, 2001;Nabbout et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to those reported from other centers and similar to our experiences with the KD in other epilepsy syndromes (Dressler et al, 2010;Kossoff et al, 2010;Maydell et al, 2001;Nabbout et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This is 33% of all children with success on the diet after 1 year. These results are in line with previous studies [8,15,16]…”
supporting
confidence: 93%
“…West syndrome and in 50% of patients with Lennox-Gastaut-syndrome. [15] In our study at Sophia Children's Hospital these results are respectively 46% and 50%. No significant differences were found between the electroclinical syndromes with respect to efficacy, however numbers are very small.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The ketogenic diet was showed to improve the seizure thresholds in mice with SCN1A mutation which is the major cause of Dravet syndrome [14]. Previous studies demonstrated a significant reduction of seizure frequency in patients with Dravet syndrome who were maintained on this diet [15,16]. Recent evidence showed that the ketones produced after MAD could reduce synaptic transmission and neuron excitability by inhibiting glutamate transport and activation of ATP-sensitive potassium channels [17].…”
Section: Discussionmentioning
confidence: 99%